1983
DOI: 10.1111/j.1469-8749.1983.tb13719.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Central Nervous System in Congenital Muscular Dystrophies

Abstract: SUMMARY Three children, two siblings and one unrelated child, with congenital muscular dystrophy with central nervous system (CNS) involvement are discussed. The siblings appeared to suffer from a relatively mild myopathy with progressive brain disease, of which brain biopsy in one showed astrocytic proliferation in the white matter. In the patient with severe muscle disease, autopsy showed widespread patchy demyelination in the white matter and developmental abnormalities in the cerebral and cerebellar cortex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…To our knowledge, histopathological investigations of cerebral white matter lesions in immunohistochemically proven MDC1A of humans are confined to two reports. In an older study, a brain biopsy of a 14-year old girl with a condition consistent with MDC1A showed intact myelin sheaths but obvious astrocytic proliferation [22], in line with the present MRS observations. An autopsy study of a 4-month-old infant with merosin-deficient CMD revealed polymicrogyria and occipital agyria with marginal neuroglial heterotopia, but normal pattern of myelination consistent with early age [8].…”
Section: Discussionsupporting
confidence: 90%
“…To our knowledge, histopathological investigations of cerebral white matter lesions in immunohistochemically proven MDC1A of humans are confined to two reports. In an older study, a brain biopsy of a 14-year old girl with a condition consistent with MDC1A showed intact myelin sheaths but obvious astrocytic proliferation [22], in line with the present MRS observations. An autopsy study of a 4-month-old infant with merosin-deficient CMD revealed polymicrogyria and occipital agyria with marginal neuroglial heterotopia, but normal pattern of myelination consistent with early age [8].…”
Section: Discussionsupporting
confidence: 90%
“…It may be that different mutations will be found to be responsible for retarded and non-retarded cases. Egger et al (1983) have suggested that the association of muscular dystrophy, cerebral malformation and white matter disease could be due to a defect in closely linked genes or to a single gene with pleiotropic effect. At present, however, this association remains unexplained.…”
Section: Discussionmentioning
confidence: 99%
“…A number of authors have described hypodense areas in the white matter of the cerebrum on CT scan, and in some cases cerebral atrophy, in a similar group of patients (Gobernado and Gimeno 1982, Egger et al 1983, Vles et al 1983, Echenne et al 1986, Martinelli et al 1987 Female pachygyria, micropolygyria, neuronal heterotopia in the outer white matter and areas of poor myelination (Fowler and Manson 1973). Similar changes were reported in two Dutch siblings by Peters and colleagues (1984).…”
mentioning
confidence: 99%